Aesthetic Preferences for Eastern and Western Traditional Visual Art: Identity Matters - Bao, Yan; Yang, Taoxi; Lin, Xiaoxiong; Fang, Yuan; Wang, Yi; Pöppel, Ernst; Lei, Quan (Frontiers in Psychology, 2016)
Western and Chinese artists have different traditions in representing the world in their paintings. While Western artists start since the Renaissance to represent the world with a central perspective and focus on salient objects in a scene, Chinese artists concentrate on context information in their paintings, mainly before the mid-nineteenth century. We investigated whether the different typical representations influence the aesthetic preference for traditional Chinese and Western paintings in the different cultural groups. Traditional Chinese and Western paintings were presented randomly for an aesthetic evaluation to Chinese and Western subjects. Both Chinese and Western paintings included two categories: landscapes and people in different scenes. Results showed a significant interaction between the source of the painting and the cultural group. For Chinese and Western paintings, a reversed pattern of aesthetic preference was observed: while Chinese subjects gave higher aesthetic scores to traditional Chinese paintings than to Western paintings, subjects from Western countries tended to give lower aesthetic scores to traditional Chinese paintings than to Western paintings. We interpret this observation as indicator that personal identity is supported and enriched within cultural belongingness. Another important finding was that landscapes were more preferable than people in a scene across different cultural groups indicating a universal principle of preferences for landscapes. Thus, our results suggest on the one hand that the way how artists represent the world in their paintings influence the way how culturally embedded viewers perceive and appreciate paintings, but that on the other hand independent of the cultural background anthropological universals are disclosed by the preference of landscapes.